The Effects of MYO-inositol and Indole Butyric Acid (IBA) on the Formation of Pineapples Root (Ananas comosus L.) from Sipahutar North Sumatera In Vitro - Hasanah, Arisah; Harahap, Fauziyah; Silaban, Ramlan (International Journal of Biological Research, 2018)
Background: Rooting of pineapple from Sipahutar in vitro is an alternative to obtain superior seeds in large quantities to meet the needs of farmers and consumers.Objective: The purpose of this study was to investigate the effect of Myo-inositol and IBA on pineapple rooting (Ananas comosus L.) from Sipahutar in vitro.Methods: The research method used a completely randomized factorial design with two factors: Factor I: Myo-inositol consisted of [4] treatment concentrations: M0 = 0 g/l, M0.02 = 0.02 g/l, M0.04 = 0.04 gr/l, M0.06 = 0.06 gr/l. Factor II: IBA growth regulators consisted of [3] treatment concentrations: IB0 = 0 ppm, IB1.5 = 1.5 ppm, IB3 = 3 ppm. The parameters observed were time of root emergence, number of roots, number of leaves, time of leaf emergence, number of tillers, and time of its emergence observed each week, while the height of tillers, shoots, and whole shoots, root length, leaf width and leaf length were observed 12 weeks after planting (WAP).Results: The result of the research showed that root time appeared on [3] WAP. The increasing number of leaves and timing of the puppiesin 1 WAP. Myo-inositol had significant effects on root counts in the 0.06 gr/l and root length on Myo-inositol treatment in the 0.04 g/l. IBA did not have a real effect on the entire observation parameters. The interactions of Myo-inositol and IBA had significant effects on root number, number of leaves, leaf length and tiller height.Conclusions: Myo-inositol and IBA had significant effects on root number, leaf number, leaf length and shoot height of pineappleâ€™s explant from Sipahutar.Â